Assessment of milk beverage functionality containing food fibers - V. I. Pak; E. P. Suchkova (Новые технологии, 2018)
Currently, there is an insufficient supply of protein and dietary fiber to the human body with food. The article considers the development of whey beverage with functional properties with the use of a cereal additive. The substantiation of the use of whey as the basis of the beverage and barley as a plant component, the formulation, the calculation of the biological value of the protein component and the supply of dietary fiber when using the recommended portion of the product is presented.